ASLAN003, a potent dihydroorotate dehydrogenase inhibitor for differentiation of acute myeloid leukemia - Zhou, Jianbiao; Yiying Quah, Jessie; Ng, Yvonne; Chooi, Jing-Yuan; Hui-Min Toh, Sabrina; Lin, Baohong; Zea Tan, Tuan; Hosoi, Hiroki; Osato, Motomi; Seet, Qihui; Ooi, Lisa A G; Lindmark, Bertil; et al. (Haematologica (Roma), 2020)
Differentiation therapies achieve remarkable success in acute promyelocytic leukemia, a subtype of acute myeloid leukemia. However, excluding acute promyelocytic leukemia, clinical benefits of differentiation therapies are negligible in acute myeloid leukemia except for mutant isocitrate dehydrogenase 1/2. Dihydroorotate dehydrogenase catalyses the fourth step of the de novo pyrimidine synthesis pathway. ASLAN003 is a highly potent dihydroorotate dehydrogenase inhibitor that induces differentiation, as well as reduces cell proliferation and viability, of acute myeloid leukemia cell lines and primary acute myeloid leukemia blasts including in chemo-resistant cells. Apoptotic pathways are triggered by ASLAN003, and it also significantly inhibits protein synthesis and activates AP-1 transcription, contributing to its differentiation promoting capacity. Finally, ASLAN003 substantially reduces leukemic burden and prolongs survival in acute myeloid leukemia xenograft mice and acute myeloid leukemia patient-derived xenograft models. Notably, the drug has no evident effect on normal hematopoietic cells and exhibits excellent safety profiles in mice, even after a prolonged period of administration. Our results, therefore, suggest that ASLAN003 is an agent targeting dihydroorotate dehydrogenase with potential in the treatment of acute myeloid leukemia. ASLAN003 is currently being evaluated in phase 2a clinical trial in acute myeloid leukemia patients.